Leadership Communication in Fostering Relationships with the Academic Community at Al-Washliyah University Medan - Umi Kalsum; Rini Dewi Andriani; Rahayu Pohan; Wulandari Intan; Devi Syukri Azhari (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
Leadership communication plays a pivotal role in shaping trust, collaboration, and institutional cohesion within higher education environments. This study investigates how leadership communication practices are implemented to foster relationships among the academic community at Al-Washliyah University Medan. Employing a qualitative descriptive design, data were gathered through in-depth interviews, direct observations, and document analysis involving university leaders, lecturers, administrative staff, and students selected via purposive sampling. The data were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. Findings indicate that effective leadership communication is characterized by transparency, dialogic engagement, empathy, and behavioral consistency. Leaders who actively utilize both formal and informal channels, supported by digital platforms, successfully cultivate a participatory culture and strengthen relational trust. However, persistent hierarchical norms, underdeveloped feedback mechanisms, and occasional misalignment between communicated policies and institutional actions remain significant barriers. The study concludes that leadership communication extends beyond mere information dissemination, functioning as a dynamic relational process that directly influences organizational climate and stakeholder engagement. Enhancing communication effectiveness requires not only the development of leaders’ interpersonal competencies but also structural reforms that institutionalize transparency, inclusive dialogue, and responsive feedback systems. These insights offer practical guidance for higher education administrators seeking to build resilient, collaborative, and sustainable academic communities.